CHALLENGES FACED BY LEARNERS WITH LEARNING DISABILITIES WITHIN THE CONTEXT OF INCLUSIVE EDUCATION: A FOCUS ON SIX PRIMARY SCHOOLS IN GLEN VIEW/MUFAKOSE EDUCATION DISTRICT OF ZIMBABWE - SAMKANGE, Dr. Wellington (IJRDO- Journal of Educational Research, 2017)
A global concern for inclusive education has been demonstrated by the different international conferences held over the past decades to address issues of equality and equity in education. Some governments have come up with laws and policies that support the implementation of inclusive education. Inclusivity entails that learners with disabilities learn together with nondisabled learners. It is important that there are checks and balances on the extent to which inclusive education is being implemented and how different groups are being catered for in schools. The paper focuses on challenges faced by learners with learning disabilities within the context of inclusive education in Glen View/Mufakose district in Harare. The study used the mixed methodology and the case study and the descriptive survey designs. Six primary schools were purposively sampled. Thirty teachers were randomly sampled and twenty learners with learning disabilities were opportunistically selected. The study used questionnaires, face-to-face interviews and observations to collect data. The study came up with the conclusions that: teachers lacked training in the handling of learners with learning disabilities; learners with learning disabilities were being wrongly labeled; the use of ability grouping had disadvantaged learners with learning disabilities; class sizes and lack of supportive devices impeded on the development of learners with learning disabilities. The study recommends that there has to be capacity building for teachers if the implementation of inclusive education is to be successful. It also recommends that communities have to mobilize resources to support the implementation of inclusive education. Lastly the Schools Psychological Services Department has to play a visible role in schools.